Physiological profile of the young Egyptian wrestlers - Saad, A. H. (World Journal of Sport Sciences, 2012)
The study aims to identify the physiological profile characteristics of the Egyptian youth wrestlers as well as to identify the differences in the physiological profile between small weights wrestlers and medium weights wrestlers in the physiological measurements under investigation, at rest and after the effort. The research sample was purposefully chosen from the winning wrestlers ranking between first to sixth position in the National Championship. Sample included 30 wrestlers aged 16:18 years, divided into two groups: 12 small weights wrestlers their weight between 50:60 kg and 18 medium weights wrestlers their weight between 66:84 kg. The most important results are the existence of set of distinctive physiological characteristics of the Egyptian wrestlers within the sample under investigation, in addition to the existence of differences, but not statistically significant between small weights wrestlers and medium weights wrestlers in the physiological variables under study.